The Scale and Structure of the Online Gig Economy - Izabela OSTOJ (Communications of International Proceedings, 2020)
The gig economy is a part of the platform economy, mediating the transactions of labour services. The online gig economy is its important element. This segment is experiencing global growth, crossing national borders. This leads to the emergence of markets that can be analyzed traditionally – both in terms of types of work performed and in terms of countries where contracts for labour services and bids from contractors originate. Their development can be monitored using data from the Oxford Internet Institute. The article aims to assess the scale and structure of the online gig economy. The analysis revealed the leading role of the USA on the demand side and its important position on the supply side, which is dominated by crowdworkers from Asia. In terms of types of activities, the global online gig economy is growing in the area of software development and technology the most dynamically.
Keywords: Digital Platforms; Gig Economy; Online Labour Index.